A Team-Based Comparative Case Study of Violence Across Care Settings for Older Adults in Two Canadian Provinces. (11th September 2021) - Herron, Rachel V.; Novek, Sheila; Kruth, Madeleine L.; Spencer, Dale; Funk, Laura; Aubrecht, Katie; Kelly, Christine; Weeks, Lori E.; Brownridge, Doug
Violence can lead to physical and psychological harm, emotional exhaustion, and burnout for paid and unpaid carers. Concomitantly, being regarded as violent, aggressive, or difficult can have a direct impact on older adults' sense of self, care relationships, and quality of care. Current research on violence and aging lacks systemic understanding of the environments and multi-level factors that precipitate or inhibit violent interactions across settings of long-term care. This research involves a multi-jurisdictional comparative research study of violence in home care and long-term care settings in two Canadian provinces (Manitoba and Nova Scotia). Study participants will include older adults, family carers, and care workers. Data collection will involve five phases, starting with document analysis and provincial surveys, and followed by remote interviews (including photo-elicitation), digital diaries, and observations. The integration of mixed methods data and comparison across provinces will generate rich explanations of the multi-level influences on violence and responses to violence as well as guide the development of an anti-violence policy framework in partnership with knowledge users. The study is approved by five university ethics committees and health authorities in each jurisdiction. All phases will be guided by a knowledge user advisory committee including older adults, family carers, healthcare workers, unions, long-term care organizations, and other relevant stakeholder groups from Manitoba and Nova Scotia. Results will be reviewed by the knowledge user advisory committee and made available through a series of reports, presentations, and journal articles.